Edukasi Wakaf Uang Bagi Penyuluh Agama Islam se-Kota Tasikmalaya - Saeful Mubarok, Acep Zoni; Rakhmat, Anwar Taufik; Rasyid, Ari Farizal; Saepulmilah, Ceceng (Edumedia Solution, 2023)
Cash waqf is a relatively new concept in Indonesia. In other nations, cash waqf has the ability to enhance the economy. In Indonesia, cash waqf has been directly announced by the President of the Republic of Indonesia, however cash waqf collecting within Indonesian society remains low in comparison to other countries. This is related to a societal lack of literacy. The Director General of Islamic Community Guidance addresses this issue by offering literacy training and education to community mobilization components such as Islamic Religious Counselors. The Siliwangi University Service Program strives to educate the community about monetary waqf through Islamic Religious Counselors. This community service is aimed at Islamic Religious Counselors who will get counseling and material on monetary waqf. The lecture technique is employed in community service activities by addressing various cash waqf materials with Islamic Religious Counselors and simulations to increase guidance. The findings of this activity show that the public's understanding of cash waqf is still lacking, and that financial institutions involved in it do not yet understand the role and potential of cash waqf in empowerment; that religious instructors play a significant role in providing guidance and socialization of cash waqf; and that waqf money has great capacity to empower people's economies. Following this monetary waqf instruction, Islamic religious instructors have a thorough grasp of cash waqf.